Uso de tecnologias da informação e comunicação para promover socialização : revisando o conceito de terceiros espaços - Ferreira, Vinícius Afonso Raimundo (Universidade Federal de São Carlos, 2015)
Third places, a term coined by sociologist Ray Oldenburg to describe places other than home (first place) or workplace (second place), places where people attend to socialize with others besides co-workers and family. Third places provide neutral ground for people to express themselves freely, necessary for civil society and civic engagement, helping to create in their regulars the feeling of belonging. Parks, cafes, bakeries, museums, theaters, churches, bars and squares are examples of third places. These places have a key role in community life forging their cultural profile. Such places are characterized by being democratic and accessible, allowing people to discuss politics, the last football game, or the next music festivals, strengthening the notion of community. However, the modern lifestyle and the potential lack of third places can lead people to be more solitary or even have fewer opportunities to attend places that promote socialization, affecting the quality of life and the sense of community. In this context, this research explores how Information and Communication Technologies (ICTs) can provide people opportunities for socializing in a third place, but unlike Oldenburg, independent of the location constraints and time, creating the phenomenon defined as thirdplaceness. Thus, it is expected to use ICTs to go beyond the traditional third places, providing opportunities for people to meet and socialize, reinforcing and extending the concept of third place, as well as confronting the stigma of isolation using technologies. To experience the support of ICTs to thirdplaceness even when there is no conventional third places to bring the community together, it is considered in this proposal the development and the use of an ICT interactive public art installation, called WishBoard. This installation explores the potential of interactions between mobile devices and public displays, allowing people to share with the community messages and their individual aspirations. This public sharing would be the opportunity for people to socialize in that space during the deployment. From the analysis of the shared messages, it was analyzed the role of ICTs to promote thirdplaceness and found evidence the cultural profile of the community in the shared anonymous messages. Considering the content of messages and the behavior of people, it was noticed that the use of public displays combined with interaction on mobile devices can promote a transformation of the place into a meeting place and conversation when they provide a way for individual self-expression and contemplation by the community that expression, causing engagement among people.
Keywords: Terceiros espaços; Thirdplaceness; Instalação interativa de arte; Socialização; Wishboard; Third places; Public display; Interactive art installation; Socialization; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO